'Stability amidst chaos': subjective re-orientation in Ivan Vyrypaev's Delhi Dance (2013) and Unbearably Long Embraces (2015). (2nd September 2018) - Wilmes, Justin
ABSTRACT: The work of the acclaimed theatre director and filmmaker Ivan Vyrypaev reveals an evolving but discernible method and thematic preoccupations. While a growing body of scholarship has examined specific aspects of Vyrypaev's work, surprisingly the central preoccupation that underlies these various devices remains relatively unformulated and unexamined. This article analyses Vyrypaev's oeuvre – with particular attention to the film Delhi Dance (2013) and the play Unbearably Long Embraces (2015) – to articulate a theory of 'subjective re-orientation' at the heart of his dramaturgy. Building upon other valuable studies of violence, affect and materiality, and performative dialogues in Vyrypaev's works, the article moves beyond a view of these devices as disparate and experimental to situate them into a more coherent artistic programme. Moreover, by considering a range of influences on his works – from his well-known zeal for Buddhism and eastern religion to a general subjective disorientation in post-Soviet Russia – this article sheds light on both Vyrypaev's sui generis dramaturgy and the resonance of his works in Russia today.